Palgrave Advances in Development Studies
X, 357 p.
Keywords: Palgrave Advances in Development Studies aims to provide readers with an understanding of the disparate theories concerning development, their assumptions and the intellectual forces underpinning them. In thirteen specially commissioned essays, leading contributors from the field of Development Studies present the relevant material to analyze and evaluate current debates about development, together with the intellectual tools to judge contemporary arguments concerning development across the world and the ability to relate theories of development to contemporary policy issues.